2017
DOI: 10.15666/aeer/1504_16051621
|View full text |Cite
|
Sign up to set email alerts
|

PROTECTIVE EFFECTS OF EXOGENOUS NITRIC OXIDE AGAINST LEAD TOXICITY IN LEMON BALM (Melissa officinalis L.)

Abstract: This research investigated the effects of exogenous sodium nitroprusside (SNP) supplementation as nitric oxide (NO) on alleviating Pb-induced oxidative damage in lemon balm (Melissa officinalis L.) plants. Pb (100, 300 and 500 μM) alone and in combination with SNP (100 and 200 μM) were given to hydroponically grown Melissa officinalis L. plants. The findings suggested that in Pbtreated plants, height, total dry weight, and chlorophyll content of leaves markedly decreased while application of 100 μM SNP allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
(58 reference statements)
2
4
0
Order By: Relevance
“…As oxidative stress is a common and severe consequence of various forms of stress, to which Pb exposure is not an exception, the role of NO in alleviating the related damages is an ongoing topic of research (Table ). In this sense, and as demonstrated by the decrease in MDA and ROS levels, concordant throughout various reports (Kopyra and Gwóźdź , Phang et al , Bai et al , Kaur et al , Amooaghaie et al , Jafarnezhad‐Moziraji et al ), this damage mitigation strategy appears promising. Nonetheless, distinct mechanisms underlying this improved tolerance can be found concerning different plants and Pb concentrations.…”
Section: No‐mediated Regulation Of Metal‐induced Oxidative Stresssupporting
confidence: 89%
See 1 more Smart Citation
“…As oxidative stress is a common and severe consequence of various forms of stress, to which Pb exposure is not an exception, the role of NO in alleviating the related damages is an ongoing topic of research (Table ). In this sense, and as demonstrated by the decrease in MDA and ROS levels, concordant throughout various reports (Kopyra and Gwóźdź , Phang et al , Bai et al , Kaur et al , Amooaghaie et al , Jafarnezhad‐Moziraji et al ), this damage mitigation strategy appears promising. Nonetheless, distinct mechanisms underlying this improved tolerance can be found concerning different plants and Pb concentrations.…”
Section: No‐mediated Regulation Of Metal‐induced Oxidative Stresssupporting
confidence: 89%
“…In spite of these beneficial effects, it is evident that when opting for a NO‐related strategy to mitigate Pb‐induced damages, special attention has to be given regarding the SNP concentration to apply. In fact, while 200 µM SNP portrayed positive effects in Amooaghaie et al (), the same concentration led to increased MDA levels and worse performance of the antioxidant defense system in Melissa officinalis (Jafarnezhad‐Moziraji et al ). Nonetheless, in the latter, Pb concentrations were about 10 times lower than in Amooaghaie et al (), which might also be affecting the success of this strategy, although Lolium perenne plants treated with similar Pb concentrations than those in Jafarnezhad‐Moziraji et al () were able to induce the antioxidant defense system (SOD, POD and APX) and reduce Pb‐related oxidative damages after being supplied with 200 µM (Bai et al ).…”
Section: No‐mediated Regulation Of Metal‐induced Oxidative Stressmentioning
confidence: 99%
“…The protective role of NO against Al-induced oxidative stress by modulating the antioxidative pathway has also been shown earlier (Wang and Yang 2005, Zhang et al 2008b, Sun et al 2015. Similar effects of H 2 S and NO have been reported to alleviate copper- (Shan et al 2012, Hu et al 2015b), boron- , Kaya and Ashraf 2015, Tepe and Aydemir 2016 and lead- (Bharwana et al 2014, Ali et al 2014b, Jafarnezhad-Moziraji et al 2017) mediated inhibition of plant growth and development (Table 1). Copper (Cu) being an essential redox component, participates in a wide range of physiological processes, e.g.…”
Section: Heavy Metal Tolerancesupporting
confidence: 62%
“…Ali et al (2014b) reported that exogenous application of H 2 S decreased Pb concentration in shoots and roots of B. napus and increased plant growth, net photosynthetic rate and development of chloroplasts within thylakoid membranes under high Pb exposures. Previous studies have also shown the ameliorative effect of NO against Pd toxicity in different plants by modulating the activities of antioxidant enzymes (Sadeghipour 2015, Jafarnezhad-Moziraji et al 2017.…”
Section: Heavy Metal Tolerancementioning
confidence: 98%
“…In this study, it is evident that exogenously applied SNP significantly enhanced the biomass yield of the shoots, regardless of Cd levels (Table 2). The alleviating effect of NO occurs because the optimum SNP concentration can directly act on the plasma‐membrane bilayers and cell wall components, causing an increase in the fluidity of the membrane and promoting the expansion of cells and growth (Xiong et al ., 2010; Wang et al ., 2013; Jafarnezhad‐Moziraji et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%